Program Legalitas Usaha Sebagai Langkah Pengembangan Umkm Di Desa Kedungdalem Kabupaten Probolinggo - Novitasari, Dwi Sukma; Taufikurrahman, Taufikurrahman; Kurniasari, Dian Nova; Setianti, Ikko Ukumi Putri; Muslimah, Izzah Asyanti; Subhanulfikri, Muhammad Faiz (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
Kedungdalem Village is one of the villages in Dringu District, Probolinggo Regency, which has many MSMEs in various types of businesses such as catering businesses, banana chip businesses, herbal medicine businesses, cake businesses, cooking spices, and so on. Of the many business actors, several business actors do not yet have business legality in the form of Business Identification Number (NIB). This is because most MSMEs in Kedungdalem Village do not fully understand the benefits of having an NIB for business legality. The method used in developing MSMEs in Kedungdalem Village is carried out through Focus Group Discussion (FGD) activities and assistance in making Business Identification Numbers (NIB). The implementation of activities includes three things, namely the presentation of material related to MSME Business Development, assistance in making NIB, and submission of business legality letters to MSME actors. The results obtained from a series of MSME development activities in Kedungdalem Village, Dringu District, namely an increase in knowledge or awareness of Kedungdalem Village MSME actors regarding the importance of business legality and business registration with OSS institutions through registration of Business Identification Numbers (NIB).